Emergence of Qualitative Research in Colombian Psychology: A Beginning that Still Does not End - Larreamendy-Joerns, Jorge; Henao, Juanita; Arango, Alexandra (Forum Qualitative Sozialforschung / Forum: Qualitative Social Research, 2006)
This article deals with the processes of emergence and evolution of qualitative research in psychology in Colombia. Two major arguments are advanced. First, these processes can only be fully understood in the light of the history of psychology in Colombia, and, at the same time, within the context of emergence and consolidation of the social sciences in Colombia. Second, the evolution of qualitative research in North American psychology coincides in some aspects with its corresponding path in Colombian psychology, even though the former exhibits some distinctive features. This article begins with a synthesis of some attempts to divide into historical periods the evolution of qualitative research in the United States. Then, it offers a historical view of psychology in Colombia. Finally, the article proposes three major historical periods to account for the emergence and evolution of qualitative research in our discipline. As a conclusion, the process of development of qualitative research in Colombia is compared to that in the United States and research challenges are proposed for Colombian scholars to address in the years to come.URN: urn:nbn:de:0114-fqs0604317